Heartrot in homogeneous stands of Acacia mangium - Halfeld-Vieira, Bernardo de Almeida; Júnior, Moisés Mourão; Tonini, Helio; Nechet, Kátia de Lima (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to report the occurrence of heartrot in homogeneous stands of Acacia mangium in the State of Roraima, Brazil. Observations of symptoms initiating from pruning wounds indicated that the artificial pruning is a predisposing factor. A survey carried out in two commercial stands showed 8 and 39% of disease incidence in three-year-old trees. Isolations performed from symptomatic trees and pathogenicity tests demonstrated that the fungus Lasiodiplodia theobromae can incite the rot development. This is the first record of A. mangium heartrot in Brazil. The disease can restrict its commercial exploration.